ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KARYAWAN CV. JAYA ABADI BENGKULU DESA BUKIT INDAH BENGKULU UTARA: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KARYAWAN CV. JAYA ABADI BENGKULU DESA BUKIT INDAH BENGKULU UTARA - Rika Dwi Yulihartika; Alexander Silaban; Heri Fariadi (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
Human resources can generate creativity, energy, and talent that help in carrying out business activities (Nawawi, 2005).Employee job satisfaction is enhanced by consideration and good relationships between superiors and subordinates.The location of this study is CV.Jaya Abadi Bengkulu, located in Bukit Indah Village, Ketahun District, Bengkulu North Province, is one of the companies engaged in the agricultural waste processing industry, from palm oil husk to palm oil husk carbon.The purpose of this study is to determine employees' long-term satisfaction with their resumes.Jaya Abadi Bengkulu and CV factors related to employee satisfaction.Jaya Abadi Bengkulu.The number of respondents for this study was 30 employees and the data collection technique used was saturation sampling or census to generate the resumes of the majority of employees. Jaya Abadi Bengkulu as a research participant. The results of CV. Jaya Abadi Bengkulu's employee satisfaction survey show an average score of 33.56, with a category of “fairly satisfied'' (26.2 -34.2). and the job itself have a significant relationship with satisfaction.